The Role of Traffic Police in Handling Congestion in Mardika Market in Ambon City - Margarita Lumaesan; Agustinus Soumokil (CV. Rayyan Dwi Bharata, 2023)
This study uses a qualitative descriptive analysis approach which aims to find out how the role of the traffic police is in dealing with congestion at the Mardika market in Ambon city. Data collection techniques in this study are observation, interviews and documentation. The results of this study indicate that the factors that cause congestion in the Mardika market are human behavior factors, and road condition factors. The role of the Traffic Police in Handling Congestion at Mardika Market includes conducting patrols, educating the traffic community and other policies in dealing with congestion at Mardika Market. The obstacles experienced by the traffic police in dealing with traffic jams are: the attitude of drivers in driving, the lack of awareness from street vendors, and the lack of public understanding of the existence of Law No. 22 of 2009. As a result, traffic jams occur along the coast of Mardika market, therefore that is the need for counseling about Law No. 22 of 2009, providing education about driving rules, as well as implementation in law enforcement in the field of traffic.